2014 IEEE 28th International Parallel and Distributed Processing Symposium 2014
DOI: 10.1109/ipdps.2014.31
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Asynchronous Linear Solvers: Provable Convergence Rate through Randomization

Abstract: Asynchronous methods for solving systems of linear equations have been researched since Chazan and Miranker's pioneering 1969 paper on chaotic relaxation. The underlying idea of asynchronous methods is to avoid processor idle time by allowing the processors to continue to make progress even if not all progress made by other processors has been communicated to them.Historically, the applicability of asynchronous methods for solving linear equations was limited to certain restricted classes of matrices, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 13 publications
0
69
0
Order By: Relevance
“…The last equality uses (14). It follows that condition (iii) of Theorem 1 holds for allρ satisfying (15).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The last equality uses (14). It follows that condition (iii) of Theorem 1 holds for allρ satisfying (15).…”
Section: Resultsmentioning
confidence: 87%
“…As also stressed in [14], very few results on convergence rates of asynchronous algorithms have appeared in the literature (see e.g., [2], [7] for exceptions). In particular, [7,Section 6.3] showed that if delays are bounded and…”
Section: Resultsmentioning
confidence: 99%
“…18) was a negative term (seeLemma 13). This term was critical in the proof of the norm convergence and FPR strong convergence criterion in Section 2.4.…”
mentioning
confidence: 99%
“…However, the iteration in (6) is sequential which might represent an issue for its implementation. Nevertheless, there are randomized and asynchronous (i.e., where any order of the updates can be followed during each iteration) versions of the Gauss-Seidel iteration, such as the one in [19]. The main conclusion is that each processor can employ the GaussSeidel iteration to compute the PageRank using updated values sent by the other processors if the web data does not belong to that processor and use the past iteration values for all the remaining ones.…”
Section: Iterationsmentioning
confidence: 99%